Study Literature Review : The Effect of Lockdown on the Covid19 Pandemic Period on Air Quality - Shofi Hikmatus Zahro (Universitas Airlangga, 2020)
Introduction: Covid19 is an infectious disease caused by the corona virus. This virus was first detected in Wuhan China. Covid19 has been defined as pandemic by the World Health Organization (WHO) since March 11, 2020. So there needs to be a policy to overcome the pandemic by implementing lockdown. The effect on the health sector one of which is environmental health includes air quality. The purpose of this literature review study is to determine the effect of the lockdown policy during the Covid19 pandemic on air quality parameters. Discussion: This research used a narrative literature review method. Selected journals that match the topic and inclusion criteria. The results of data analysis show that there is an effect of the lockdown policy during the Covid19 pandemic, namely an increase in AQI and O3 . Meanwhile, decreased concentration occurs in the PM10; PM2.5; NO2 ; CO; and SO2 parameters. Conclusion: Lockdown policy provided a big influence on the air quality in Sale City Marocco and Sao Paulo Brazil. Lockdown policies during the Covid19 period strongly influenced the concentration of NO2 .6